Kisspeptin as a master player in the central control of reproduction in mammals: An overview of kisspeptin research in domestic animals. (27th March 2013) - Okamura, Hiroaki; Yamamura, Takashi; Wakabayashi, Yoshihiro
Abstract: The hypothalamo‐pituitary‐gonadal (HPG) axis is the regulatory system for reproduction in mammals. Because secretion of gonadotropin‐releasing hormone (GnRH) into the portal vessels is the final step at which the brain controls gonadal activities, the GnRH neuronal system had been thought to be central to the HPG axis. A newly discovered neural peptide, kisspeptin, has opened a new era in reproductive neuroendocrinology. As shown in a variety of mammals, kisspeptin is a potent endogenous secretagogue of GnRH, and the kisspeptin neuronal system governs both the pulsatile GnRH secretion that drives folliculogenesis, spermatogenesis and steroidogenesis, and the GnRH surge that triggers ovulation in females. The kisspeptin neuronal system is therefore considered a master player in the central control of mammalian reproduction, and kisspeptin and related substances could therefore be valuable for the development of novel strategies for the management of fertility in farm animals. To this end, the present review aimed to summarize the current research on kisspeptin signaling with a focus on domestic animals such as sheep, goats, cattle, pigs and horses.